The Impact of Capital Market on Economic Growth: A Malaysian Outlook - Nordin, Sabariah; Nordin, Norhafiza (International Journal of Economics and Financial Issues, 2016)
This study analyzes the influence of the stock market and the debt market on the Malaysian economy. The Johansen-Juselius co-integration test reveals the existence of co-integrating relationship between real GDP per capita, stock market and debt market. The VECM long-run results show that both, the stock market and the debt market, have positive and significant influence on the Malaysian economy. The stock market is found to exert greater influence on the Malaysian economy compared to the debt market. Furthermore, unlike the debt market, the stock market is found to exert uni-directional causality on the economy. Since both markets have significant and positive influence on the Malaysian economy, the policy makers should implement appropriate measures to be able to fully utilize the opportunity created by both markets, especially the liquidity condition of the stock market as it influences an investor’s financial and investment decision making process. Keywords: Capital Market, Stock Market, Debt Market JEL Classifications: G1, O1